Fucoidan Hydrogels Significantly Alleviate Oxidative Stress and Enhance the Endocrine Function of Encapsulated Beta Cells (Adv. Funct. Mater. 35/2021). (26th August 2021) - Reys, Lara L.; Vaithilingam, Vijayaganapathy; Sthijns, Mireille M. J. P. E.; Soares, Eduardo; Rademakers, Timo; de Vries, Rick; Mohammed, Sami G.; de Bont, Denise; Jetten, Marlon J.; Hermanns, Carolin; Filho, Omar Paulino da Silva; Stell, Adam; et al.
Abstract : Fucoidan Hydrogels In article number 2011205, Tiago H. Silva, Aart A. van Apeldoorn, and co‐workers explore the potential of fucoidan, a marine sulfated polysaccharide, for pancreatic islet encapsulation. Fucoidan has high fucose contents with sulfate groups, demonstrating potent antioxidant properties and significantly alleviating oxidative stress and enhancing the viability and function of encapsulated beta cells. A fucoidan‐based hydrogel is thus assessed as biomaterial for bioengineered immunoprotective beta cell replacement systems.